2016
DOI: 10.23856/1815
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Human Capital Management in the Conditions of Innovative Economy

Abstract: The article identifies the key challenges of human capital development of domestic enterprises. The comparative analysis of innovative and traditional approaches to human capital management is performed. The organizational and economic mechanism of the enterprise human capital management in the conditions of innovative economy is grounded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, in [11,12], it is noted that various team members improve the company's activities by introducing wider bases of knowledge and experience. In [13,14], it was shown that with increasing (gender) diversity in groups the available cognitive resources are expanded. Research materials [15,16] indicate that if cognitive resources are used effectively, these resources are transformed into diverse perspectives that can contribute to the emergence of alternative solutions (diversification of solutions).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in [11,12], it is noted that various team members improve the company's activities by introducing wider bases of knowledge and experience. In [13,14], it was shown that with increasing (gender) diversity in groups the available cognitive resources are expanded. Research materials [15,16] indicate that if cognitive resources are used effectively, these resources are transformed into diverse perspectives that can contribute to the emergence of alternative solutions (diversification of solutions).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, along with the fundamental scientific achievements obtained in [4][5][6][7][8][9][10][11][12][13][14][15][16], the fragmentation of research results that have practical relevance to determining the importance of the influence of the gender factor on resource provision of the enterprise is worth noting.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation